CHINA DIGITAL AS COUNTERWEIGHT ASIA-PACIFIC CENTURY - Bayu Altair (Kajian Asia Pasifik, 2020)
China's digital transformation has been made China's digital economic capabilities awake sharply. The digitalization of China is determined by several factors which are based on the current globalization. The Chinese government also plays an active role in accelerating the domestic digital transition process and core in way of intensive cooperation with countries in the Asia Pacific region. Changes in Chinese orientation using a digital approach create anxiety for the United States of America with the emergence of the China axis in the region. The framework of the article uses the concept of digitalization to describe the process of digital transformation in China, then Neo-liberalism theory of Robert Keohane & Joseph Nye to explain the pattern of China's cooperation with the region and the Balance of Power as the middle-range theory to emphasize the emergence of China's digital axis in Asia-Pacific. Using descriptive qualitative methods and collecting literature study data, this article emphasizes the analysis of the magnitude effect of digitizing China as a new axis in the Asia Pacific region as competitors in the United States and Australia. The digitalization and intensification of cooperation believed to be the main variable in balancing the political economy axis at the regional level. Keywords: China Digital, Cooperation, Digital Economic Capability Abstrak Transformasi digital China telah membuat kapabilitas ekonomi China meningkat tajam. Digitalisasi China dideterminasi oleh beberapa faktor yang didasari oleh adanya arus globalisasi. Pemerintah China juga berperan aktif mempercepat proses transisi digital domestik serta menjadi kunci jalannya kerjasama kerjasama intensif dengan negara dikawasan Asia Pasifik Perubahan orientasi China menggunakan pendekatan digital menciptakan kekhawatiran bagi Amerika Serikat akan munculnya poros China dikawasan. Kerangka pemikiran artikel menggunakan konsep Digitalisasi untuk menggambarkan proses transformasi digital di China, teori Neoliberalisme versi Robert Keohanne & Joseph Nye untuk menjelaskan pola kerjasama China dengan negara dikawasan dan teori Balance of Power sebagai middle-range teori untuk menekankan kemunculan poros digital China di Asia-Pasific. Dengan menggunakan metode deskriptif kualitatif dan pengumpulan data studi literatur, artikel ini menekankan pada analisis besarnya pengaruh digitalisasi China sebagai poros baru dikawasan Asia Pasifik sebagai kompetitor Amerika Serikat dan Australia. Digitalisasi dan intensifikasi kerjasama diyakini menjadi variabel utama penyeimbang poros ekonomi politik dilevel regional. Kata Kunci: Digital China, Kerjasama, Kapabilitas Digital Ekonomi